2019
DOI: 10.1126/science.aax7852
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-mediated live imaging of genome editing and transcription

Abstract: We report a robust, versatile approach called CRISPR live-cell fluorescent in situ hybridization (LiveFISH) using fluorescent oligonucleotides for genome tracking in a broad range of cell types, including primary cells. An intrinsic stability switch of CRISPR guide RNAs enables LiveFISH to accurately detect chromosomal disorders such as Patau syndrome in prenatal amniotic fluid cells and track multiple loci in human T lymphocytes. In addition, LiveFISH tracks the real-time movement of DNA double-strand breaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
212
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(219 citation statements)
references
References 32 publications
7
212
0
Order By: Relevance
“…Here, we have repurposed the RNA-guided RNA endonuclease activity of Cas13d in mammalian cells against emergent viral targets, SARS-CoV-2 and IAV, in our PAC-MAN strategy. This expands the applications of CRISPR-Cas13 systems in addition to their uses for diagnostics such as SHERLOCK and live-cell imaging [30][31][32][33] . Prior work showed Cas13a/b systems could inhibit ssRNA viruses including influenza, which is consistent with our observed high efficiency of SARS-CoV-2 reporter and IAV inhibition using the PAC-MAN approach 31 .…”
Section: Discussion and Perspectivesmentioning
confidence: 95%
“…Here, we have repurposed the RNA-guided RNA endonuclease activity of Cas13d in mammalian cells against emergent viral targets, SARS-CoV-2 and IAV, in our PAC-MAN strategy. This expands the applications of CRISPR-Cas13 systems in addition to their uses for diagnostics such as SHERLOCK and live-cell imaging [30][31][32][33] . Prior work showed Cas13a/b systems could inhibit ssRNA viruses including influenza, which is consistent with our observed high efficiency of SARS-CoV-2 reporter and IAV inhibition using the PAC-MAN approach 31 .…”
Section: Discussion and Perspectivesmentioning
confidence: 95%
“…A variant of FISH (CAS-FISH), based on fluorescent dCas9 RNPs instead of DNA hybridization probes(Deng et al, 2015), showed rapid, cost-effective and convenient multi-color labelling of genomic loci, in fixed cells. More recently, use of dCas9 RNPs with fluorescent CRISPR RNAs (crRNAs) achieved high SNR detection of highly-repetitive genomic loci in cell lines, as well as in primary human cells(Wang et al, 2019). The latter study also illustrated the potential of RNP-based approaches for medical diagnostics and for genomic imaging in systems that are not readily amenable to genetic manipulations.…”
mentioning
confidence: 93%
“…Future developments of low-cost methods to prepare in vitro transcribed pools of fluorescent gRNAs, such as using dye-binding aptamers(Autour et al, 2018;Filonov et al, 2014), could enable increased detection SNR, due to the rapid degradation of background gRNAs that are not "protected" in a target DNA-bound dCas9:RNA:DNA ternary complex. Finally, combining our DNA targeting RNP system with RNA targeting CRISPR proteins, such as dCas13(Wang et al, 2019;Yang et al, 2019), would facilitate simultaneous imaging of cis-elements, target genes and nascent transcripts, as well as various other chromatin associated RNAs. Such direct visualization approaches would transform our ability to probe the links between genome organization and gene expression regulation as well as the nuclear organization, dynamics and function of non-coding regulatory RNAs.…”
mentioning
confidence: 99%
“…* * * Type VI CRISPR enzymes have recently been identified as programmable RNA-guided, RNA-targeting Cas proteins with nuclease activity that allow for target gene knock-down without altering the genome. In addition to target RNA knock-down 1-9 , Cas13 proteins have been used to enable viral RNA detection systems 7,9-11 , site-directed RNA editing 12 , demethylation of m 6 Amodified transcripts 13 , RNA live-imaging 14,15 , and modulation of splice site choice as well as cleavage and polyadenylation site usage 5,16,17 .Cas13 proteins are guided to their target RNAs by a single CRISPR RNA (crRNA) composed of a direct repeat (DR) stem loop and a spacer sequence (guide RNA) that mediates target recognition by RNA-RNA hybridization. Although Cas13 enzymes exert some non-specific collateral nuclease activity upon activation 4-6,10,18 , they have greatly reduced off-target activity in cultured cells compared to RNA interference 2,5,12 .…”
mentioning
confidence: 99%
“…* * * Type VI CRISPR enzymes have recently been identified as programmable RNA-guided, RNA-targeting Cas proteins with nuclease activity that allow for target gene knock-down without altering the genome. In addition to target RNA knock-down 1-9 , Cas13 proteins have been used to enable viral RNA detection systems 7,9-11 , site-directed RNA editing 12 , demethylation of m 6 Amodified transcripts 13 , RNA live-imaging 14,15 , and modulation of splice site choice as well as cleavage and polyadenylation site usage 5,16,17 .…”
mentioning
confidence: 99%